Student centered pedagogy: from the perspective of professional accounting education - Mohammed, Nor Farizal; Abdullah, Azizah (2018)
This paper, through qualitative research, examined the pedagogical approach employed in the professional accounting education.This paper investigated whether student-centered pedagogy as recommended by prior literature is ideal for the professional accounting education from the lens of professional accounting lecturers, in an emerging country where the learning and political environment differs from the western countries. Data were collected from semi-structured interviews of professional accounting lecturers in the only public university in Malaysia that conducts professional accounting programs. While the literature recommends students-centered pedagogy to be adopted, the results revealed that the lecturers favored the mixed approaches. The main challenge in professional accounting education is the urge to pass the examination. This is the critical factor that is halting students-centered pedagogy to be adopted. The findings offer important implications for regulators, policy-makers and education educators in devising the accounting education system in emerging countries like Malaysia and Asia-Pacific region, where the learning environment is more passive